Mathematical Refractive Thinking Ability in Multivariable Calculus: Instrument Design and Quality of Use - Yenti, Isra Nurmai; Kusumah, Yaya S; Dahlan, Jarnawi Afgani (Universitas Sarjanawiyata Tamansiswa, 2021)
Mathematical refractive thinking ability must be given in every lecture because it is needed in decision making. This study aims to produce a quality mathematical refractive thinking ability instrument, especially for calculus material. Instrument quality is measured in terms of validity and reliability. Content validity, construct validity and face validity were assessed by three material experts. The instrument was tested by 32 mathematics education students to measure empirical validity and reliability. This research resulted in three items of mathematical refractive thinking ability tests that are valid and have instrument reliability in the medium category.